2012
DOI: 10.1063/1.4768547
|View full text |Cite
|
Sign up to set email alerts
|

The thermal analysis of paraffin wax in a box-type solar cooker

Abstract: In this study, the potential use and effectiveness of paraffin wax in solar cooker during the daylight and/or late evening hours is experimentally investigated. For these experiments, a box-type solar cooker was constructed by filling paraffin wax with metal shavings. The side- and sub-surface temperatures of the paraffin wax in the cooker are continuously measured during June and July 2011. The effect of the reflector angle on the thermal efficiency of the cooker is tested with different isolation conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
7
0
1
Order By: Relevance
“…3.1.3 Analysis of the properties of the forced separation products 3.1.3.1 Infrared spectral analysis of the products. The absence of absorption peaks above 3000 cm À1 and within the range of 1500-2800 cm À1 in the infrared spectra of the raw materials (2) and forced separation fractions indicated that they were hydrocarbon substances without unsaturated bonds and carbon heterocyclic bonds, which also proved that there were no chemical reactions occurring during the forced separation process. The absorption peaks at 2916 cm À1 and 2848 cm À1 were ascribed to the alkyl stretching vibrations of -CH 2 and -CH 3 , respectively.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…3.1.3 Analysis of the properties of the forced separation products 3.1.3.1 Infrared spectral analysis of the products. The absence of absorption peaks above 3000 cm À1 and within the range of 1500-2800 cm À1 in the infrared spectra of the raw materials (2) and forced separation fractions indicated that they were hydrocarbon substances without unsaturated bonds and carbon heterocyclic bonds, which also proved that there were no chemical reactions occurring during the forced separation process. The absorption peaks at 2916 cm À1 and 2848 cm À1 were ascribed to the alkyl stretching vibrations of -CH 2 and -CH 3 , respectively.…”
Section: Resultsmentioning
confidence: 89%
“…2.1.2 Raw material (2). Paraffin wax (melting point 64.3 C) was fabricated by PetroChina Fushun Petrochemical Company.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yuksel et al [55] used paraffin wax in a double-glazed box-type SC (Figure 18). In that experiment, 3.5 kg of paraffin wax was filled in the space clawed between aluminum plates and metal shavings.…”
Section: Box-type Solar Cooker With Thermal Energy Storage Conceptmentioning
confidence: 99%
“…) the PCM was filled below the absorbing plate. Yuksel et al (2012) experimentally investigated the potential use and effectiveness of paraffin wax in a solar hot-box cooker during daylight and late evening hours. In this design, the rate of heat transfer from the PCM to the cooking pot during the discharging mode of the PCM was slow, and more time was required for cooking food in the evening.…”
Section: Oven Solar Cookers Using Lhtesmentioning
confidence: 99%